Thinking volleyball - Hebert, Mike 1944- (Champaign, IL Human Kinetics, 2014)
"Hall-of-fame coach Mike Hebert spent years learning the secrets to success--among the most important is that you should never stop learning. In Thinking Volleyball, he goes beyond the development of motor skills to provide a unique cerebral look at how athletes learn. Hebert also introduces the strategies behind his reading defense approach, which will give your team an advantage against any opponent. Regardless of how talented your players are, a positive environment that includes a solid mutual trust among everyone involved with the program is vital for your program both on and off the court." -- book cover
Learning and decision making -- Structuring and running the program -- Embracing a playing style -- Honing vital skills -- Thinking about team defense -- Drawing a blueprint for offense -- Promoting a positive gym culture -- Strengthening team trust -- Coaching the match -- Thinking outside the box.
Includes index.
Keywords: Volleyball